Standardized radial approach reduces access site complications. Issue 1 (January 2015) - Markovic, Sinisa; Imhof, Armin; Kunze, Markus; Rottbauer, Wolfgang; Wöhrle, Jochen
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to evaluate the occurrence of complications by Doppler sonography after radial access for cardiac catheterization in a prospective observational registry. Background The radial approach for cardiac catheterization is being used with increasing frequency. In randomized trials, the risk of bleeding was lower with radial access compared with femoral access. However, there are still concerns in terms of the radial access because of reported high rates of radial artery occlusion (RAO) up to 30%. Materials and methods In this prospective observational registry, a total of 369 procedures were performed using a standardized radial approach in terms of sheath size, anticoagulation, and postinterventional hemostasis. The rates of RAO, hematoma, and vascular complications were assessed the day after catheterization. Results A diagnostic procedure was performed in 25.7% and a coronary intervention in 74.3% of patients. Sheath size was 5 Fr in 12.2% (N=45) or 6 Fr in 87.8% (N=324). Doppler sonography showed RAO in 3.8% (N=14/369), with no difference between the 5- and the 6-Fr sheath (2.2 vs. 4.0%, P=0.56). A hematoma of 5 cm or more was documented after two (0.5%) procedures. There was no need for any blood transfusion or surgery. A small hematoma (every hematoma <5 cm) was observed in 16.0% (N=59). There was no statistical difference in the frequency of RAO, hematoma, or vascular complications between procedures performed with 5-Fr or less or 6-Fr sheaths and the use of dual antiplatelet therapy or oral anticoagulation. Conclusion Radial access for coronary catheterization is effective and safe. With a standardized approach, the rates of bleeding events and RAOs are low.